New evidence of megafaunal bone damage indicates late colonization of Madagascar - Anderson, A; Clark, G; Haberle, S; Higham, T; Nowak-Kemp, M; Prendergast, A; Radimilahy, C; Rakotozafy, LM; Ramilisonina,; Schwenninger, J-L; Virah-Sawmy, M; Camens, A (Public Library of Science, 2018)
The estimated period in which human colonization of Madagascar began has expanded recently to 5000–1000 y B.P., six times its range in 1990, prompting revised thinking about early migration sources, routes, maritime capability and environmental changes. Cited evidence of colonization age includes anthropogenic palaeoecological data 2500–2000 y B.P., megafaunal butchery marks 4200–1900 y B.P. and OSL dating to 4400 y B.P. of the Lakaton’i Anja occupation site. Using large samples of newly-excavated bone from sites in which megafaunal butchery was earlier dated >2000 y B.P. we find no butchery marks until ~1200 y B.P., with associated sedimentary and palynological data of initial human impact about the same time. Close analysis of the Lakaton’i Anja chronology suggests the site dates <1500 y B.P. Diverse evidence from bone damage, palaeoecology, genomic and linguistic history, archaeology, introduced biota and seafaring capability indicate initial human colonization of Madagascar 1350–1100 y B.P.